Co-production of evidence for policies in Thailand: from concept to action. (15th February 2021) - Tangcharoensathien, Viroj; Sirilak, Supakit; Sritara, Piyamitr; Patcharanarumol, Walaiporn; Lekagul, Angkana; Isaranuwatchai, Wanrudee; Wittayapipopsakul, Woranan; Chandrasiri, Orana
Abstract : Viroj Tangcharoensathien and colleagues apply the "triangle that moves the mountain" to analyse the co-production of evidence for health policy making in Thailand